The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1117/1.jmi.2.1.015501
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic density measurements are not affected by mammography system

Abstract: Abstract. Mammographic density (MD) is a significant risk factor for breast cancer and has been shown to reduce the sensitivity of mammography screening. Knowledge of a woman's density can be used to predict her risk of developing breast cancer and personalize her imaging pathway. However, measurement of breast density has proven to be troublesome with wide variations in density recorded using radiologists' visual Breast Imaging Reporting and Data System (BIRADS). Several automated methods for assessing breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…The current analysis was conducted using images previously used with radiologists based in America using the BI‐RADS scale . That study by our group found a higher, moderate, inter‐reader agreement (κ = 0.57) for USA based American board of Radiology certified radiologists.…”
Section: Discussionmentioning
confidence: 91%
“…The current analysis was conducted using images previously used with radiologists based in America using the BI‐RADS scale . That study by our group found a higher, moderate, inter‐reader agreement (κ = 0.57) for USA based American board of Radiology certified radiologists.…”
Section: Discussionmentioning
confidence: 91%
“…Although such methods eliminate between-reader variations in readings, many only work on a single image type (often raw digital images [25]), but others can be applied across multiple types [8, 26]. It is possible that there would be between-system differences in automated measures, particularly volumetric measures due to differences in breast positioning and therefore breast thickness [27], but not all studies have found this [28]. In the future, as further processing algorithms are developed, MD differences between raw and processed images are likely not only to persist but also to change.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mean and median time between images was 7.1 and 4 weeks, respectively, and it is unlikely that the PD of the women in this study would have perceptibly and significantly changed during this short amount of time. 7,25,26 Furthermore, it is possible that changes in positioning technique could affect the observed density between the Siemens and Hologic images for a given woman; however, such differences are unlikely to be systematic based on screening or diagnostic imaging status.…”
Section: Discussionmentioning
confidence: 99%
“…6 Differences in vendor-specific image acquisition technology can result in images from some vendors having a wider range of pixel intensities and darker appearance in fatty regions and brighter appearance in dense tissue regions compared to other vendors even when variations in positioning are minimized. 7 The resulting differences in display may affect perception of the amount and distribution of breast tissue and, therefore, the visual assessment of PD. As such, vendor-specific differences in the appearance of the "for presentation" mammography images routinely reviewed in clinical care may contribute to the unreliability of visual assessments of PD, particularly in cases when data are pooled across multiple sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation